Supporting or alienating students during their transition to Higher Education: Mathematically relevant trajectories in the contexts of England and Norway. (2016) - Pampaka, Maria; Pepin, Birgit; Sikko, Svein Arne
Highlights: We focus on transition to mathematically demanding courses in university in UK and Norway. Data come from longitudinal surveys in both countries. We validated measures proxies of students' subjective alienation experience. Measurement results indicated measurement invariance issues. Separate analysis showed some common patterns in sources of alienation from maths. Abstract: Drawing on our projects of transition to mathematically demanding subjects in UK Higher Education and an extension of this work in Norway, we explore the measurement of various pedagogical and learning aspects of students' transition into Higher Education. We focus on experiences of engagement, and alienation, which we claim can offer an enhanced view on student learning experiences. Our analysis is based on longitudinal surveys of students entering different programmes in UK (N = 1778), and Norwegian (N = 721) universities. Validation is performed within the Rasch measurement framework, which indicated problems in establishing measurement invariance. Cross-sectional analysis of the two datasets, then, revealed consistent patterns in the process of alienation from mathematics as well as some systemic mechanisms that can help alleviate that.